To solve the equation \( 13(6x - 9) = -33 \), you can follow these steps in the correct order:
-
Distribute the 13 on the left side: \[ 13 \cdot 6x - 13 \cdot 9 = -33 \] which simplifies to: \[ 78x - 117 = -33 \]
-
Add 117 to both sides to isolate the term with \( x \): \[ 78x - 117 + 117 = -33 + 117 \] which simplifies to: \[ 78x = 84 \]
-
Divide both sides by 78 to solve for \( x \): \[ x = \frac{84}{78} \] which simplifies to: \[ x = \frac{14}{13} \]
So the correct order of steps to solve the equation \( 13(6x - 9) = -33 \) is:
- Distribute the 13.
- Add 117 to both sides.
- Divide both sides by 78.
Thus, the final solution is \( x = \frac{14}{13} \).